FP-LAPW investigation of structural, electronic, linear and nonlinear optical properties of ZnIn2Te4 defect-chalcopyrite - Ayeb, Y.; Ouahrani, T.; Khenata, R.; Reshak, Ali H.; Rached, D.; Bouhemadou, A.; Arrar, A. (Elsevier B. V., 2010)
Link to publisher's homepage at http://www.elsevier.com/